Reliability and validity of the Chester step test in patients with interstitial lung disease - Alves, A. (2022)
The Chester Step Test (CST) is a simple and inexpensive field test, which requires minimal physical space to assess exercise capacity. Such characteristics make the CST suitable to be used in different settings, however, its measurement properties in patients with interstitial lung diseases (ILD) are unknown. A cross-sectional study was conducted in patients with ILD. First, a CST-1 and a 6-minute walk test (6MWT) were performed. After 48-72 hours, a CST-2 was repeated. A 2nd rater was present in one of the sessions. Relative reliability was measured using intraclass correlation coefficient (ICC1,1 and ICC2,1). Absolute reliability was determined using standard error of measurement (SEM), minimal detectable change at 95% confidence interval (MDC95) and the Bland-Altman method. The values of SEM and MDC95 were also expressed as a percentage of the mean. Construct validity was explored using Spearman correlation coefficient (rs) between the number of steps taken in the best CST and the distance performed in the 6MWT. Sixty-six patients with ILD (65.5±12.9 years; 48.5%men; FVC 79.4±18.8pp; DLCO 49.0±18.3pp) participated in the study. Relative (ICC 0.95-1.0) and absolute reliability were excellent without evidence of systematic bias. The SEM and MDC95 were 11.8 (14.7%) and 32.6 steps (40.7%), respectively. The correlation between CST and 6MWT was significant, positive, and high (rs=0.85, p=0.001). The CST is a reliable and valid test and might be especially useful to assess exercise capacity in patients with ILD in limited space environments.